Teacher Identity Formation: A Vernacular Discourse Analysis of Television Public Service Advertisement - Florence Yulisinta; Rustono Farady Marta; Hana Panggabean (Universitas Padjadjaran, 2023)
Background: The influence of technology and media on teachers’ beliefs and self-concepts is substantial. The social identity theory explains how an individual’s perception of themselves as a group member influences their social identity. Purpose: This study aims to examine the analysis of vernacular discourse in public service announcements (PSA) from two perspectives: cultural syncretism and pastiche. Methods: The methodology utilized in this study is vernacular discourse analysis with a critical paradigm-based qualitative approach. The objects of this study were two PSA videos of the Ministry of Education (MOE) Singapore. Results: The vernacular discourse analysis reveals that cultural and social contexts influence teachers’ rhetoric, with sociocultural and linguistic conditions reinforcing educational hegemony in the PSA videos of Singapore. Conclusion: MOE’s PSA videos shape teachers’ social identity by employing persuasive strategies to promote teachers’ roles and self-concepts based on the belief that student and societal success begins with the teacher. Implications: Theoretically, this study implies that media can shape teachers’ social identities. The practical implications of this study are using PSA videos to align the role and self-concept of Indonesian teachers, demonstrating how the noble but less prestigious teaching profession shapes the next generation. Additionally, media can be utilized to enhance the quality of education in Indonesia.